One Does Not Fit All: European Study Shows Significant Differences in Value-Priorities in Clean Sport - Woolway, Toby; Elbe, Anne-Marie; Barkoukis, Vassilis; Bingham, Kevin; Bochaver, Konstantin; Bondarev, Dmitriy; Hudson, Andy; Kronenberg, Lara; Lazuras, Lambros; Mallia, Luca; Ntovolis, Yannis; Zelli, Arnaldo; et al. (Frontiers in Sports and Active Living, 2021)
Doping violates the Spirit of Sport and is thought to contradict the values which underpin this spirit. Values-based education (VBE) has been cited as a key element for creating a clean sport culture across age groups. Culturally relevant VBE requires understanding of the values that motivate athletes from different countries to practice their sport and uphold clean sport values. WADA's new International Standards for Education makes this study both needed and timely. Overall, 1,225 athletes from Germany, Greece, Italy, Russia, and the UK responded to measures assessing their general values, Spirit of Sport values, and their perceived importance of “clean sport”. MaxDiff analysis identified the most important values to participants based on their respective country of residence. Correlation analysis was conducted to assess the relationship between importance of clean sport and Spirit of Sport values. There were significant differences between participant nationality and their perceived importance of clean sport [F(4, 1,204) = 797.060, p < 0.000], the most important general values (p < 0.05), and Spirit of Sport values (p < 0.05). Moderate positive correlations were observed between the perceived importance of clean sport and honesty and ethics (r = 0.538, p < 0.005) and respecting the rules of sport (r = 0.507, p < 0.005). When designing the values-based component of anti-doping education programs, athletes' different value-priorities across countries should be considered.